2021
DOI: 10.3390/ijms22115951
|View full text |Cite
|
Sign up to set email alerts
|

Serratia symbiotica Enhances Fatty Acid Metabolism of Pea Aphid to Promote Host Development

Abstract: Bacterial symbionts associated with insects are often involved in host development and ecological adaptation. Serratia symbiotica, a common facultative endosymbiont harbored in pea aphids, improves host fitness and heat tolerance, but studies concerning the nutritional metabolism and impact on the aphid host associated with carrying Serratia are limited. In the current study, we showed that Serratia-infected aphids had a shorter nymphal developmental time and higher body weight than Serratia-free aphids when f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Enterobacteriaceae is one of the important dominant taxa in the gut microbiota of many insects ( Wang et al, 2014 ; Yun et al, 2018 ; Raza et al, 2020 ). Enterobacteriaceae are involved in insect metabolism ( Pers and Hansen, 2021 ; Zhou et al, 2021 ), insect resistance or susceptibility to parasites, and pathogens and insecticides ( Oliver et al, 2003 ; Álvarez-Lagazzi et al, 2021 ; Polenogova et al, 2021 ) and play an important role in the host adaptability and reproduction of insects ( Shi et al, 2012 ; Wang et al, 2020b ). Pectobacterium , a clade of Enterobacteriaceae , is known as a function of nitrogen fixation ( Behar et al, 2005 , 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteriaceae is one of the important dominant taxa in the gut microbiota of many insects ( Wang et al, 2014 ; Yun et al, 2018 ; Raza et al, 2020 ). Enterobacteriaceae are involved in insect metabolism ( Pers and Hansen, 2021 ; Zhou et al, 2021 ), insect resistance or susceptibility to parasites, and pathogens and insecticides ( Oliver et al, 2003 ; Álvarez-Lagazzi et al, 2021 ; Polenogova et al, 2021 ) and play an important role in the host adaptability and reproduction of insects ( Shi et al, 2012 ; Wang et al, 2020b ). Pectobacterium , a clade of Enterobacteriaceae , is known as a function of nitrogen fixation ( Behar et al, 2005 , 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the level of triglyceride was severely decreased after knocking down FAS1 in the mosquito Aedes aegypti [ 11 ]. In Serratia-infected Acyrthosiphon pisum , the triglyceride content was reduced by feeding with dsFASN1 compared with the control [ 29 ]. Therefore, the present study demonstrates that FAS is not only responsible for fatty acid synthesis, but also affects the lipid dynamic in insects.…”
Section: Discussionmentioning
confidence: 99%
“…Here, this can be exemplified by the lipogenic scd1a and scd1b enzymes, which becomes especially interesting in the case of scd1a given that a recent study revealed reliable epigenetic mechanisms (changes in DNA methylation rates of the scd1a promoter) by which the nutrition of parents can shape the s cd1a gene expression in the gilthead sea bream offspring (Perera et al, 2020 ). The extent to which this can be favored by changes in the gut microbiota remains unknown, but interestingly, the up-regulation of scd1 genes in the fish fed with the non-PAP diet was associated with OTUs assigned to Serratia nematodiphila (NoPAP, 1.02%) and Brevinema andersonii (NoPAP 0.1%; CTRL and PAP <0.01%), giving these taxa a role as intestinal SCFA producers in humans (Parada Venegas et al, 2019 ) and enhancers of fatty acid metabolism in insects (Zhou et al, 2021 ). The case of B. andersonii merits further attention, as this species belongs to Spirochaetesphylum, which colonizes the gut gilthead sea bream microbiome to a large extent with advancing age (11% in 4-year-old individuals) (Piazzon et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%